The The Impact of Organization culture and Work Environment on Employee Engagement and It’s Implication on Employee Performance of The Automotive Industry In Jakarta, Indonesia. - Machmed Tun Ganyang, Ganyang (Archives of Business Research, 2019)
This study aims to determine and analyze the impact of organization culture , work environment on employee engagementt and it’s implications on employee performance. This research uses quantititaive approarch. Population of this research is the whole employee of the automotive industry and sample is 86 respondents. The result of this hypothesis test show that (1) Organization culture has a direct, positive, and statistically significant impact on employe engagement; (2)Work environment has a direct, positive and statistically significant on employee engagement; (3) Employee engagement has a direct positive and statistically significant on employee performance.